Yamunapur in Bhita, India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Photos from the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) research benchmark site in Yamunapur, India.